Assessment of professional baseball players aerobic exercise performance depending on their positions - Yang, S.-W. (The Journal of Strength and Conditioning Research, 2014)
This study reports the average and SD of professional baseball players' cardiorespiratory endurance, maximum oxygen consumption, oxygen consumption during anaerobic threshold, maximum oxygen consumption of anaerobic threshold %, maximum heart rate, and heart rate of anaerobic threshold. We also report the comparison between pitchers and fielders. Considering the total number of results, percentile was used and results were classified into 5 grades. One professional baseball players' organization with more than 14 years of experience participated in this study. First, we observed that the average pitchers' VO2max was 53.64 ml/kg/min, whereas the average fielders' was 52.30 ml/kg/min. These values were lower than other sports players. Second, in case of the VO2AT, pitchers showed 39.35 ml/kg/min and fielders showed 39.96 ml/kg/min. %VO2AT showed a significant difference of 71.13% between pitchers and fielders-pitchers, whereas fielders showed 73.89% (p < 0.01). Third, maximal heart rates were measured at 188.69 b/min (pitchers) and 187.79 b/min (fielders). These were lower than college baseball players and higher than other sports players. In conclusion, both professional baseball pitchers and fielders should be aware of the necessity of systematic cardiorespiratory endurance data analysis. Moreover, baseball teams, athletic trainers, and coaches should also be aware of the importance of cardiorespiratory endurance.